Transformasi Pendidikan Kewirausahaan: Sinergi Akademik dan Industri untuk Pertumbuhan Bisnis Berkelanjutan (SDG 8) - Swaramarinda, Darma Rika; Hamdani, Fajri; Kusumaningrum, Alifah; Suhendry, Bayu; Isa, Badrul; Putra, Andrew Krishna; Fathiyyah, Sabil Alvin; Taqy, Farras (Abdimas Indonesian Journal, 2025)
This community service program aims to transform entrepreneurship education through the synergy between academic institutions and the industrial sector to foster sustainable business growth. The international collaboration between Universitas Negeri Jakarta (UNJ), Indonesia, and Universiti Teknologi MARA (UiTM), Malaysia, serves as a strategic foundation for designing adaptive, innovative, and relevant educational approaches that respond to modern business challenges.The program focuses on enhancing students’ competencies in business leadership, digital marketing strategies, financial management, and professional networking. The activities are conducted through training sessions, mentoring, and hands-on guidance involving lecturers and industry practitioners as main facilitators. The program takes place at the UNJ campus, engaging students from diverse entrepreneurial backgrounds. Evaluation is carried out through pre- and post-surveys to measure competence improvement, as well as through tangible outputs such as training documentation, scientific articles, and educational video recordings. Preliminary results indicate an increased understanding among participants regarding business digitalization, the use of technology in business management, and their readiness to adapt within the global entrepreneurial ecosystem. The program also supports the achievement of SDG 8 (Decent Work and Economic Growth) by empowering students to create independent and sustainable employment opportunities. By employing a student- and industry-oriented approach, this initiative not only provides short-term competency improvement but also contributes to developing a collaborative entrepreneurship education model that can be replicated in other academic institutions.